A Non-Linear Autoreggresive Distributed Lag Analysis of the Triple Deficit Hypothesis in the Mena Region - Raouf, Engy (Asian Economic and Financial Review, 2020)
This paper focuses on assessing the validity of the triple deficit hypothesis in fourteen Middle Eastern and Northern African (MENA) countries between 1999 and 2018, using a non-linear autoregressive distributed lag (NARDL) model. Although many studies have used different methods to address this issue, they often conclude that the relationship between the budget deficit, the current account deficit, and the saving-investment gap is a symmetric relationship. This study claims that it is possible to shed new light on this issue by introducing non-linearity into studies on the relationship between these three deficits using the recently developed NARDL technique. This paper provides evidence for the existence of a non-linear relationship between the current account deficit, budget deficit, and saving-investment gap. It also shows that the triple deficit hypothesis is valid in the long-term. On the contrary, the relationship between external and internal deficits is negative in the short-term, which means that there is a triple divergence.